Improving Effect of Cooperative Learning-Based Physical Education on Children's Negative Psychology - Luobin Zhang; Fei Yang; Qianqian Yang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Modern education has the critical responsibility of holistically fostering children's psychological and moral development. Psychological health has direct effects on the growth and development of children and indirect effects on the quality of talent training in society. Physical activity improves the negative psychology of youngsters (CNP). Both domestic and international scholars have focused on investigating and implementing cooperative learning-based innovative and successful physical education. This research presents the structural equation model (SEM) to investigate the enhancing influence of cooperative learning-based physical education (CL-PE) on CNP and analyzes children's psychology using pertinent data mining technologies and a model. First, a structural equation model (SEM) was developed to examine how CL-PE influences CNP, and the interacting, moderating, and mediating effects were investigated in depth. The proposed SEM was then transformed into a self-organized path-constrained neural network (SOPCNN), the latent variables were computed, and the observable indices were summarized. Three schools' preschool-aged students were polled to compile the set of test samples. The results of an experiment indicate that adding cooperative learning to physical education might successfully attenuate children's negative psychology.